Autoantibodies in Chronic Obstructive Pulmonary Disease - Wen, Lifang; Krauss-Etschmann, Susanne; Petersen, Frank; Yu, Xinhua (Frontiers in Immunology, 2018)
Chronic obstructive pulmonary disease (COPD), the fourth leading cause of death worldwide, is characterized by irreversible airflow limitation based on obstructive bronchiolitis, emphysema, and chronic pulmonary inflammation. Inhaled toxic gases and particles, e.g. cigarette smoke, are major etiologic factors for COPD, while the pathogenesis of the disease is only partially understood. Over the past decade, an increasing body of evidence has been accumulated for a link between COPD and autoimmunity. Studies with clinical samples have demonstrated that autoantibodies are present in sera of COPD patients and some of these antibodies correlate with specific disease phenotypes. Furthermore, evidence from animal models of COPD has shown that autoimmunity against pulmonary antigens occur during disease development and is capable of mediating COPD-like symptoms. The idea that autoimmunity could contribute to the development of COPD provides a new angle to understand the pathogenesis of the disease. In this review article, we provide an advanced overview in this field and critically discuss the role of antibodies in the pathogenesis of COPD.